Uji Metode Naive Bayes Classifier dalam Pembagian Bantuan Langsung Tunai oleh Program Keluarga Harapan - Panjaitan, Syarifah Utari; Siregar, Machrani Adi Putri; Harleni, Silvia (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2024)
Direct Cash Assistance (DCA) can be understood as giving a sum of money (cash) to the poor through a village fund budget issued by the government. The DCA Program for Target Households (PTH) in its implementation must directly touch and provide direct benefits to the poor (which are categorized as PTH), encourage shared social responsibility and be able to foster public trust in the government in really paying attention to PTH. The Naive Bayes classifier is a classification method that can be used in the distribution of Direct Cash Assistance (DCA) by the Family Hope Program (FHP). The data used in this study were obtained from the East Sei Kepayang sub-district and the Asahan District Social Service. The data taken is only data obtained in 2022 and in branches sourced from the village fund budget issued by the government. The results showed that based on predetermined test data, the probability of "yes" assistance was 0.0066650391 while the probability of "no" assistance was 0, so that the results of the classification "yes" for this data were obtained.